(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
House is a social concept its nature and cognition are varying with caste, class religion and region (Unni, 1965). The word has been used as a synonym for census house, which is defined as, “a building or a part of a building having a separate main entrance from the road or common courtyard or staircase, etc., used or recognized as a separate unit. It may be occupied or vacant. It may be used for a residential or non-residential purpose or both (Census of India, 2001). In a simplistic way, a house is a ‘shelter’ to live in. It is one of the basic human entitlements which connect its occupant with the society. The study is based on primary and secondary data. The primary data has been collected by using well prepared schedules and personal interviews conducted to the head of family. It is concluded that the pacca houses in the village Mundhal Khurd belong to upper castes and other backward castes people who have a good quality and specious houses rather than the low caste people. It is noted that most of pacca houses belong to Punjabi, Khati, Lohar, Jat, Brahman and Nai castes of village and these castes have good socially and economically status. It is observed that the mixed houses are diminishing day to day replacing by the pacca houses due to improvement in economic conditions of inhabitants and availability and suitability of local building material in recent years.